2023
DOI: 10.7717/peerj.15676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracts from various parts of invasive Solidago species on the germination and growth of native grassland plant species

Abstract: Allelopathy is an important factor influencing whether an invasive plant species can become successfully established in a new range through disrupting the germination and growth of native plant species. Goldenrods (Solidago species) are one of the most widespread invasive taxa in Central Europe of North American origin. Owing to their high environmental impact and wide distribution range, invasive Solidago species should be controlled in Europe, and the areas invaded by them should be restored. Numerous studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Others found that S. canadensis affects the growth and seed germination of tested plants (Lactuca sativa, Morus alba, Pharbitis nil, Brassica campestris, Lepidium sativum, and others) [71][72][73]. The allelopathic effect was also observed in the research by Perera et al [74] where S. canadensis leaf and flower extracts caused lower germination and seedling growth of different grassland plant species such as Festuca rubra L., Phleum pratense L., Poa pratensis L., Lotus corniculatus L., Trifolium repens L., and Silene flos-cuculi (L.) Greuter & Burdet.…”
Section: Behind the Invasiveness Of S Canadensismentioning
confidence: 62%
“…Others found that S. canadensis affects the growth and seed germination of tested plants (Lactuca sativa, Morus alba, Pharbitis nil, Brassica campestris, Lepidium sativum, and others) [71][72][73]. The allelopathic effect was also observed in the research by Perera et al [74] where S. canadensis leaf and flower extracts caused lower germination and seedling growth of different grassland plant species such as Festuca rubra L., Phleum pratense L., Poa pratensis L., Lotus corniculatus L., Trifolium repens L., and Silene flos-cuculi (L.) Greuter & Burdet.…”
Section: Behind the Invasiveness Of S Canadensismentioning
confidence: 62%
“…Before litter decomposition, S. canadensis litter exhibited a stronger allelopathic effect than native litter on lettuce (Lactuca sativa) (He et al, 2022). Our previous study on the response of native grassland species to allelopathic species revealed that leaves and flowers of Solidago species have stronger inhibition effects than stems, roots, and rhizomes (Perera et al, 2023). Therefore, Solidago allelopathy will alter the neighbouring species which may change the decomposition of litter.…”
Section: Discussionmentioning
confidence: 99%
“…In such young plants, the roots are much smaller than the green parts. In addition, extracts from the green parts of goldenrods affect other plants more than those from the roots 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Note that we use the term “weed” for all non-crop plants, as these plants are not wanted by farmers as they lead to crop contamination. Both goldenrods and walnuts have been reported to have allelopathic effects on other plant species 34 36 , 38 . Also, both goldenrod and walnut often co-occur with crops 15 , 16 and weeds 4 , 14 in agricultural landscapes, and agricultural activities commonly incorporate damage and transportation of both plant tissues into the soil.…”
Section: Introductionmentioning
confidence: 99%